Corticolous Lichen Communities and Their Bioindication Potential in an Urban and Peri-Urban Ecosystem in the Central Region of Colombia (2024)
The richness, composition, abundance, and correlation with the atmospheric oxide concentrations of the community of corticolous lichens in the urban and peri-urban areas of the city of Ibagué (Colombia) were evaluated, selecting 25 individuals of the four most abundant phorophyte species. Twenty-nine lichen taxa grouped in 13 families and 17 genera were recorded, with a higher lichen coverage and taxa richness in the urban area. A non-metric multidimensional scaling (NMDS) analysis showed the conformation of two lichen communities associated with the urban and peri-urban areas of the city, and variation in composition among the phorophyte species. Exclusive and indicator taxa were found for both zones, as well as associations between variables through the application of a general linear model. Higher concentrations of atmospheric gases CO, SO2, NO2, and O3 were found in the urban zone, and positive/negative relationships with some lichen taxa. There is high variability in the response of the lichen assemblage of urban and peri-urban ecosystems to environmental effects, with substantial or minimal changes in the variables of richness, coverage, and phorophyte association, and according to their interaction with atmospheric oxides, the patterns of potential tolerant and/or sensitive species are formed for their implementation in bioindication studies.